Emotional Intelligence and Doctor’s Counterproductive Work Behavior: The Mediating Role of Leader Member Exchange Quality - et al., Budiman (International Journal of Advanced Science and Technology, 2019)
We investigated the moderating function of the Leader-Member Exchange Quality (LMXQ) in the relationship of Emotional Intelligence and Doctor’s Counterproductive Behaviour. Accordingly, the purpose of this research is to examine the immediate influence of leader-member exchange quality and emotional intelligence on counterproductive work performance. This analysis was administered by employing data collected from 408 Indonesians’ doctors of a government hospital. Measuring tools adopted from the Counterproductive Work Behavior-Checklist (CWB-C) including of 45 items, Emotional Competency Inventory (ECI) consisting of 50 items and Multidimensional Instrumental Leader-Member Exchange (MDM-LMX), data were investigated applying Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) with SPSS version 22 and AMOS version 23. The results revealed that the hypothesized model has the best-fit standards, with the specification model presenting a more reliable goodness-of-fit. Mainly, the outcomes confirmed that leader-member exchange quality, together with emotional wit, carries a direct negative and vital impression on counterproductive work performance. This investigation further supported that there is a negative indirect and notable effect factor of emotional intelligence on counterproductive work behaviour through leader-member exchange quality as mediators. Further, predictor factors namely emotional intelligence, added 23%, and leader-member exchange quality gave 23% on variance counterproductive work behaviour. In conclusion, emotional intelligence and leader-member exchange quality was the deciding constituent for counterproductive work practice. The value of counterproductive work behaviour in this research offers to supplement the theories of organizational behaviour and adds to the execution of human resource development and administration within the company.